Evolução tectônica e estratigráfica das bacias da margem continental do Uruguai - Pérez, Ethel Morales [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The continental margin of Uruguay is a typical divergent margin, generated as the result of the breakup of Gondwana and later opening of the Atlantic Ocean. It is located in the southern extensional segment of the Atlantic margin, where the opening came from the south to the north, during the Jurassic-Early Cretaceous. Three sedimentary basins are located on the continental margin of Uruguay: the Punta del Este Basin, the southernmost part of the Pelotas Basin and the Oriental del Plata Basin. The crustal architecture of the Uruguayan margin presents characteristics of volcanic type passive margins, with the development of SDR wedges and the presence of a high velocity lower crust. The thickness of the continental crust decrease progressively in the strike direction of the Uruguayan continental margin and the passage of continental-oceanic crust came closer to the coastal line in the same direction. Mohorovicic unconformity presents a sharp inflection in the central and northern sectors of the Uruguayan continental margin (Pelotas Basin), associated with thinning of the continental crust and more gradual in the southern sector (Punta del Este Basin). This inflection coincides with the shelf break and the largest gravity anomaly present in the continental margin of Uruguay for each sectors. Fourteen depositional sequences were mapped on the Uruguayan continental margin, using the sequence stratigraphy as a basin analysis method. These depositional sequences were grouped into four phases of evolution: prerift (Paleozoic), rift (Jurassic-Early Cretaceous), transition (Barremian-Aptian) and postrift (Aptian-Present). Each of these phases has a specific structural configuration and stratigraphic architecture, depending of the type of basin, tectonic elements, sediment supply, rate of subsidence and sea level changes. During the geological evolution of the Uruguayan continental margin a migration of depocenters occurred, towards northeast....

A margem continental uruguaia é uma típica margem divergente gerada pela fragmentação do supercontinente Gondwana e posterior abertura do Oceano Atlântico. Localiza-se no segmento extensional sul da margem atlântica, onde a abertura ocorreu de sul para norte, durante o Jurássico-Cretáceo Inferior. Três bacias sedimentares estão presentes na margem continental uruguaia: a Bacia de Punta del Este, a porção mais austral da Bacia de Pelotas e a Bacia Oriental del Plata. A estrutura crustal da margem continental uruguaia apresenta feições características de margens passivas do tipo vulcânico, com desenvolvimento de cunhas de SDR e presença de um corpo de alta velocidade sísmica na base da crosta. Para nordeste, seguindo o strike da margem uruguaia, é notável a progressiva diminuição da espessura da crosta continental e a maior proximidade com a linha de costa da passagem de crosta continental-crosta oceânica. A descontinuidade de Mohorovicic apresenta inflexão brusca, associada ao adelgaçamento da crosta continental, no setor central e setentrional da margem uruguaia (Bacia de Pelotas), e mais gradual no setor meridional (Bacia de Punta del Este), a qual se correlaciona com a quebra da plataforma continental e a maior anomalia gravimétrica para cada um dos setores. Utilizando a estratigrafia de sequências como método de análise de bacia, catorze sequências deposicionais foram mapeadas na margem uruguaia, pertencentes a quatro fases de evolução: pré-rifte (Paleozoico), rifte (Jurássico-Cretáceo Inferior), transição (Barremiano- Aptiano) e pós-rifte (Aptiano-Presente). Cada uma dessas fases apresenta configuração estrutural e arquitetura estratigráfica particulares, decorrentes do tipo de bacia, dos elementos tectônicos presentes, do aporte sedimentar, da taxa de subsidência e das variações do nível do mar. Durante a evolução geológica da margem continental uruguaia ocorreu uma migração de depocentros...
Keywords: Geology, Stratigraphic; Geologia estratigráfica; Geologia estrutural; Margens continentais